Resposta :
Resposta:
x² + 8x + 74
Explicação passo a passo:
(x + 7)² - (x + 4).(x - 4) + (x - 3)²
vamos resolver cada binômio separadamente
(x + 7)²=> x² + 14x + 49
(x + 4).(x - 4) => x² - 16
(x - 3)²=> x²- 6x + 9
substituindo na expressa temos:
x² + 14x + 49 -( x² - 16) + ( x²- 6x + 9)=> x² + 14x + 49 - x² + 16 + x²- 6x + 9=> 2x²- x² +14x - 6x + 49 +16 + 9 => x² + 8x + 74
Resposta:
x² + 8x + 74
Explicação passo a passo:
(x + 7)² - (x + 4).(x - 4) + (x - 3)²
x² + 2x . 7 + 7² - (x² - 4²) + x² - 2x . 3 + 3²
x² + 14x + 49 - (x² - 16) + x² - 6x + 9
x² + 14x + 49 - x² + 16 + x² - 6x + 9
x² + 14x + 49 + 16 - 6x + 9
x² + 8x + 49 + 16 + 9
x² + 8x + 74